ChemInform Abstract: Dumbbells of Five‐Connnected Silicon Atoms and Superconductivity in the Binary Silicides MSi3 (M: Ca, Y, Lu). Issue 2 (9th January 2013) - Schwarz, Ulrich; et al., et al.
Abstract The new metastable title compounds are prepared by high pressure/high temperature reaction of the elements (Ta ampules, 12—15 GPa, 900—1400 K).